Characterization of Gd-rich precipitates in a fully lamellar TiAl alloy. (August 2017) - Wang, Xiaodong; Luo, Ruichun; Liu, Fang; Zhu, Fan; Song, Shuangxi; Chen, Bin; Zhang, Xiwen; Zhang, Ji; Chen, Mingwei
Abstract: We report microstructural characterization of a Gd-modified TiAl alloy with a fully lamellar structure by utilizing Cs-corrected transmission electron microscopy. Two types of Gd-contained precipitates, Gd2 O3 and Al2 Gd, with sizes ranging from several nanometers to micrometers were detected at grain boundaries and lamellar interfaces. Atomic-scale images reveal a well-defined crystallographic relationship between the nano-scale Al2 Gd precipitates and γ-TiAl while Gd2 O3, formed from TiAl melt during solidification and precipitated from α phase, is incoherent with TiAl matrix. The microstructural characterization provides direct evidence that the microstructure refinement of the Gd-modified TiAl is mainly from both oxide and intermetallic precipitates. Graphical abstract: